2007
DOI: 10.1038/sj.clpt.6100192
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Justice and Autonomy in Clinical Research With Healthy Volunteers

Abstract: In clinical research, ethics review generally first examines whether study risks are reasonable in light of benefits provided. Through informed consent, then, prospective subjects consider whether the risk/benefit balance and procedures are reasonable for them. Unique ethics issues emerge in clinical research with healthy volunteers. Certain types of studies only recruit healthy volunteers as participants. Phase 1 studies, for example, including first time in human studies of investigational drugs and vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 31 publications
(69 reference statements)
3
49
1
Order By: Relevance
“…[2][3][4][5][6] Over one third of participants in this study experienced no adverse events. Of the 64% of participants who did, the majority (nearly 85%) of adverse events were mild.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Over one third of participants in this study experienced no adverse events. Of the 64% of participants who did, the majority (nearly 85%) of adverse events were mild.…”
Section: Discussionmentioning
confidence: 99%
“…Yet patient advocates, bioethicists, and researchers criticize phase I research because they claim that healthy participants are exposed to high risks of serious harms with no possibility of clinical benefit. [2][3][4][5][6][7] This assumption is obviated when non-oncology phase I research poses few serious risks to participants but is reinforced by episodes such as the TeGenero case in which six healthy individuals in a phase I study experienced life threatening reactions. [8][9][10] Robust studies exist on the risks and clinical benefits of phase I oncology trials that enroll patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed that a personal approach by skilled clinical trial staff leading to development of a good relationship with study participants during the trial can have a large impact on recruitment of new participants in the study through recommendations from earlier participants, as well as repeat participation in future studies 4 9. Almeida et al 4 reported that ‘word of mouth’ was the source of information in 94.9% participants.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Third, payments may result in some individuals regarding repeated research participation as a full-time occupation that might pose high risks and offers few rewards. 5,6 Fourth, some express concern that phase I trials enroll low-income participants who endure high trial risks but have limited access to the medical products they help develop. 69 …”
Section: Introductionmentioning
confidence: 99%